DESAIN JARINGAN KOMPUTER PADA PERUSAHAANYANG SERING BERUBAH LETAK MEJA KERJA ATAU BERPINDAH PINDAH LOKASI KANTOR DENGAN WIFI DIRECT - Fahmil Triaga; Fajrillah; Roberto Kaban (Jurnal Ilmiah Informatika, 2018)
Similar to Bluetooth technology, Wifi direct is a connectivity concept within the network that allows all devices connected in the network to directly access data directly from one to another. Wifi direct has advantages in terms of connectivity, range and speed of data transfer, so the future will have an opportunity to replace the existing tekonolgi today. Bluetooth is the most likely technology to be rivaled. Currently, connectivity with bluetooth monopolizes the mobile connections of gadgets as well as computer devices such as headphones, mice, keyboards, printers and more. The device connectivity reach WiFi Direct is much farther and stronger than Bluetooth, therefore WiFi Direct is often referred to as a heavy rival of Bluetooth. In terms of data transmission, direct wifi can transfer large amounts of data, WiFi Direct can be used to access and play online games and be connected to various devices such as PCs, Smart TVs, printers, digital cameras and other smart devices without the need for data cables. The use of Wifi direct is also one of the solutions as a medium of data transmission for the office that often change the layout of the room and switch desks.